2021
DOI: 10.1016/j.ajo.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Presence of SARS-CoV-2 Viral RNA in Aqueous Humor of Asymptomatic Individuals

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 17 publications
(24 reference statements)
1
36
0
2
Order By: Relevance
“…In the present study, we detected SARS-CoV-2 RNA in 50% of the examined conjunctival specimens and in 30% of the examined IVBs. Our results are in accordance with previous studies that found SARS-CoV-2 RNA within the eye [ 18 , 19 , 24 ]. In other studies, SARS-CoV-2 RNA was not detected in conjunctiva and vitreous [ 17 , 20 , 21 , 23 , 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we detected SARS-CoV-2 RNA in 50% of the examined conjunctival specimens and in 30% of the examined IVBs. Our results are in accordance with previous studies that found SARS-CoV-2 RNA within the eye [ 18 , 19 , 24 ]. In other studies, SARS-CoV-2 RNA was not detected in conjunctiva and vitreous [ 17 , 20 , 21 , 23 , 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, SARS-CoV-2 RNA could be detected intraocularly up to 78 h after death and up to 94 days after the first positive test. A recent report by Koo et al showed that SARS-CoV-2 RNA was present in the aqueous humor of asymptomatically infected subjects despite negative nasal swab tests [ 24 ]. This raises the question whether and how long SARS-CoV-2 can persist in immune-privileged niches like the eye without causing any symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of these parameter values between different visits showed no significance, except for ACV. SARS-CoV-2 virus presence has been reported in the anterior chamber and cornea tissue [ 10 13 ]. Yan et al reported the presence of nucleocapsid protein antigens on the cells of the conjunctiva, iris, and trabecular meshwork of a patient with a COVID-19 infection, and these antigens were absent on the specimens from the control patient [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SARS-CoV-2 RNA and proteins was reported in the anterior chamber and corneal tissue following COVID-19 infection [ 10 13 ]. Moreover, some incompatible reports were on the presence of viruses on the ocular surface [ 14 ].…”
Section: Introductionmentioning
confidence: 99%